2013
DOI: 10.1111/pai.12098
|View full text |Cite
|
Sign up to set email alerts
|

Transient impact of omalizumab in pollen allergic patients undergoing specific immunotherapy

Abstract: Eighteen weeks' treatment of omalizumab in combination with SIT in patients with SAR and comorbid SAA reduced the symptom load during the treatment period but showed no prolonged effect during treatment with SIT only. A slight increase in lung function (FEV1) in patients formerly treated with the omalizumab/SIT combination therapy should encourage further evaluation of long-term effects of omalizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 16 publications
0
50
0
10
Order By: Relevance
“…A multicenter placebo-controlled randomized trial evaluating omalizumab or placebo in 140 subjects as an added therapy to SCIT over 2 years for the treatment of seasonal AR during the pollen season demonstrated that the concomitant use of omalizumab reduced symptom severity by 39% over SCIT alone and also improved asthma control and asthma and AR quality of life [145]. A subsequent study by the same group failed to demonstrate sustained effects of omalizumab throughout the remaining duration of SCIT for pollen allergy [146]. Preliminary data for the use of omalizumab as adjunct therapy to treat cow milk allergy and bee venom allergy have shown some encouraging results but larger well-designed studies have not been conducted to date.…”
Section: Adjunct Therapy Omalizumabmentioning
confidence: 93%
“…A multicenter placebo-controlled randomized trial evaluating omalizumab or placebo in 140 subjects as an added therapy to SCIT over 2 years for the treatment of seasonal AR during the pollen season demonstrated that the concomitant use of omalizumab reduced symptom severity by 39% over SCIT alone and also improved asthma control and asthma and AR quality of life [145]. A subsequent study by the same group failed to demonstrate sustained effects of omalizumab throughout the remaining duration of SCIT for pollen allergy [146]. Preliminary data for the use of omalizumab as adjunct therapy to treat cow milk allergy and bee venom allergy have shown some encouraging results but larger well-designed studies have not been conducted to date.…”
Section: Adjunct Therapy Omalizumabmentioning
confidence: 93%
“…45 Omalizumab therapy also improved the symptom relief seen with SCIT, but this improvement did not continue after the omalizumab was discontinued. [45][46][47] These studies have not addressed the optimal pretreatment time for omalizumab to impart added safety to SCIT. A reasonable pretreatment based J ALLERGY CLIN IMMUNOL PRACT VOLUME -, NUMBERon the data to date suggests an 8-to 12-week course of omalizumab before allergen immunotherapy.…”
Section: Immunotherapymentioning
confidence: 97%
“…Clinical evidence also suggests that it ameliorates other allergic co-morbidities such as food allergy, eczema and rhinoconjunctivitis. Treatment with Omalizumab could also be used to protect against anaphylaxis during start-up of immunotherapy in severely allergic children [98,99].…”
Section: Omalizumabmentioning
confidence: 99%